2019
DOI: 10.1007/s42452-019-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Green preparation of chlorine-doped graphene and its application in electrochemical sensor for chloramphenicol detection

Abstract: A green but efficient synthesis approach for chlorine-doped reduced graphene oxide (Cl-RGO) was developed. The chlorine-doping and reduction was achieved in one-step by refluxing graphene oxide solution in concentrated hydrochloric acid (8 M, 120 °C) under N 2 atmosphere. X-ray photoelectron spectroscopy analysis revealed that the Cl content was 1.01 at.% in the Cl-RGO. Electrochemical measurements indicated that the Cl-RGO modified glass carbon electrode showed enhanced electrochemical conductivity and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…To date, electrochemical biosensors have been used to detect CAP, TC, AMP and PCN in milk, honey, chicken, and beef [ 172 , 173 , 174 , 175 , 176 ]. Wang et al [ 172 ] developed a green and efficient synthesis approach for chlorine-doped reduced graphene oxide (Cl-RGO) and constructed a highly selective electrochemical sensor for CAP based on Cl-RGO. The sensor has excellent reproducibility (102.4–103.5%) and storage stability and has been successfully used for CAP detection in milk samples.…”
Section: Advanced Methods For Detectionmentioning
confidence: 99%
“…To date, electrochemical biosensors have been used to detect CAP, TC, AMP and PCN in milk, honey, chicken, and beef [ 172 , 173 , 174 , 175 , 176 ]. Wang et al [ 172 ] developed a green and efficient synthesis approach for chlorine-doped reduced graphene oxide (Cl-RGO) and constructed a highly selective electrochemical sensor for CAP based on Cl-RGO. The sensor has excellent reproducibility (102.4–103.5%) and storage stability and has been successfully used for CAP detection in milk samples.…”
Section: Advanced Methods For Detectionmentioning
confidence: 99%
“…The sensor potential against commonly present structures such as glucose, uric acid, and ascorbic acid was tested and confirmed the applicability of graphene oxide/ZnO nanocomposite sensor in real sample applications. In a later work, there was an attempt to improve graphene electrochemical behavior through doping with heteroatom [ 110 ]. Subsequently, reduced graphene oxide was doped using chlorine to fabricate a novel electrochemical sensor for the detection of pharmaceutical samples, calf plasma, milk, water, and veterinary drugs containing chloramphenicol.…”
Section: Antibiotics Electrochemical Detection Methodsmentioning
confidence: 99%
“…Besides this, the SEM image of Cl-GP1 indicates that the formation of more edge sites of the graphene powder sheets is more signicant than for Cl-GP2 and Cl-GOP, as this can be related to the higher doping of Cl atoms. 51,60 TEM analysis shows the presence of wrinkled and high transparency Cl-doped graphene-based powder layers, typical of thin graphene structures. It has been found that the thickness between the Cl-GP1 layers is 0.33 nm, and multilayered graphene powder sheets can be observed in the HRTEM images.…”
Section: Microscopic Characterization Of Cl-doped Graphenebased Powdersmentioning
confidence: 99%
“…This can be attributed to the increased amount of chlorine doping as a result of the completion of the reduction process during synthesis in the graphene powder structure. 39,60 Fig. 6 TEM images of (a) Cl-GP1, (b) Cl-GP2, and (c) Cl-GOP.…”
Section: Microscopic Characterization Of Cl-doped Graphenebased Powdersmentioning
confidence: 99%